A mixed‐method systematic review and meta‐analysis of mental health professionals' attitudes toward smoking and smoking cessation among people with mental illnesses. (3rd May 2016) - Sheals, Kate; Tombor, Ildiko; McNeill, Ann; Shahab, Lion
Abstract: Background and aims: People with mental illnesses and substance abuse disorders are important targets for smoking cessation interventions. Mental health professionals (MHPs) are ideally placed to deliver interventions, but their attitudes may prevent this. This systematic review therefore aimed to identify and estimate quantitatively MHPs attitudes towards smoking and main barriers for providing smoking cessation support and to explore these attitudes in‐depth through qualitative synthesis. Methods: The online databases AMED, EMBASE, Medline, PsychINFO, HMIC and CINAHL were searched in March 2015 using terms relating to three concepts: 'attitudes', 'mental health professionals' and 'smoking cessation'. Quantitative or qualitative studies of any type were included. Proportions of MHPs' attitudes towards smoking and smoking cessation were pooled across studies using random effects meta‐analysis. Qualitative findings were evaluated using thematic synthesis. Results: Thirty‐eight studies including 16 369 participants were eligible for inclusion. Pooled proportions revealed that 42.2% [95% confidence interval (CI) = 35.7–48.8] of MHPs reported perceived barriers to smoking cessation interventions, 40.5% (95% CI = 30.4–51.0) negative attitudes towards smoking cessation and 45.0% (95% CI = 31.9–58.4) permissive attitudes towards smoking. The most commonly held beliefs were that patients are not interested in quitting (51.4%, 95% CI = 33.4–69.2) and that quitting smoking is too much for patients to take on (38%, 95% CI = 16.4–62.6). Qualitative findings were consistent with quantitative results, revealing a culture of smoking as 'the norm' and a perception of cigarettes as a useful tool for patients and staff. Conclusions: A significant proportion of mental health professionals hold attitudes and misconceptions that may undermine the delivery of smoking cessation interventions; many report a lack of time, training and confidence as main barriers to addressing smoking in their patients.